Whole genome sequencing of isoniazid monoresistant clinical isolates of Mycobacterium tuberculosis reveals novel genetic polymorphisms. (March 2022) - Gupta, Shraddha; Kumar, Chanchal; Shrivastava, Kamal; Chauhan, Varsha; Singh, Anupriya; Arora, Rohan; Giri, Astha; Cabibbe, Andrea Maurizio; Sharma, Naresh Kumar; Spitaleri, Andrea; Cirillo, Daniela Maria; Bose, Mridula; et al.
Abstract: In an attempt to uncover genotypic indicators for isoniazid (INH) resistance in M. tuberculosis, in addition to the canonical mutations in genes associated with INH resistance, including katG, inhA and fabG promoter; we analyzed, two INH monoresistant isolates, ASTS24/13 (INHR1) and SHR1/14 (INHR2). Targeted Sanger sequencing detected a canonical mutation at katG315 only in INHR2. Infection of THP-1 cells and exposure to antituberculosis drugs led to two-fold increase in the minimum inhibitory concentration of INH in INHR2. Whole genome sequences revealed that INHR1 and INHR2 belonged to Delhi Central Asian Strain and East African Indian lineages, respectively. The sequences were compared with INH susceptible isolates with the same lineage as the INH monoresistant strains. INHR1 had a novel unique mutation STOP420Trp in the efflux pump gene Rv0849, while INHR2 had a novel mutation Arg579Ser in efflux pump gene mmpL5. C omparison of lipid associated genes showed novel mutations in INHR1 in fadE16, fadD3 and fbpD; while INHR2 had mutations in fadE1, Rv0145, Rv1425, fadD9 and mmaA3 . Both isolates also demonstrated novel mutations in cell wall associated genes. Our study highlights the importance of searching for alternate mechanisms of INH resistance that may contribute to the development of more comprehensive diagnostic tools.